2006
DOI: 10.1634/theoncologist.11-90001-42
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Capecitabine in First-Line Treatment for Patients with Metastatic Breast Cancer

Abstract: Capecitabine is an important drug in the therapeutic armamentarium for metastatic breast cancer. A comprehensive worldwide clinical trial program involving >10,000 patients with locally advanced and metastatic breast cancer has provided evidence for the current treatment strategies. On the basis of data demonstrating consistent activity across several trials in patients with heavily pretreated breast cancer, capecitabine was approved in the U.S. in 1998 for the treatment of patients with metastatic disease res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…Metronomic dosing results in low plasma concentrations of capecitabine and its intermediates and simulates a low-dose infusion of 5-FU (18). When administered daily, capecitabine efficacy is superior to intravenous 5-FU infusion in the treatment of anthracycline-resistant metastatic breast cancer (19) and is approved for colorectal cancer treatment (20). Recent studies of metronomically dosed capecitabine with gemcitabine show comparable or modestly improved survival times and good tolerability (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Metronomic dosing results in low plasma concentrations of capecitabine and its intermediates and simulates a low-dose infusion of 5-FU (18). When administered daily, capecitabine efficacy is superior to intravenous 5-FU infusion in the treatment of anthracycline-resistant metastatic breast cancer (19) and is approved for colorectal cancer treatment (20). Recent studies of metronomically dosed capecitabine with gemcitabine show comparable or modestly improved survival times and good tolerability (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Chemotherapeutic regimens containing taxanes and anthracyclines are the current standard of care for hormone-refractory MBC, and are being used earlier in the course of the disease with increasing frequency [2][3][4]. Sequential single-agent therapies including capecitabine, gemcitabine, and vinorelbine are preferred to combination regimens for MBC progressing after anthracyclines and taxanes, with capecitabine being the only approved monotherapy [5][6][7][8][9]. While these agents exhibit antitumor activity in this patient population, none showed a survival benefit either alone or in combination with other drugs [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Sequential single-agent therapies including capecitabine, gemcitabine, and vinorelbine are preferred to combination regimens for MBC progressing after anthracyclines and taxanes, with capecitabine being the only approved monotherapy [5][6][7][8][9]. While these agents exhibit antitumor activity in this patient population, none showed a survival benefit either alone or in combination with other drugs [8,9]. The prognosis is particularly unfavorable for patients with a reduced performance status who are typically more symptomatic and less responsive to treatment than those with a good performance status [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The phase II studies of gastric and NSCLC have also shown promising results using the above combinations [19][20][21][22]. The maximum concentration of vorinostat tolerable by human body was determined using two phase I pharmacokinetic and pharmacodynamics studies in combination with FOLFOX or 5-FU/LV chemotherapy regimens [23,24] in CRC.…”
Section: Discussionmentioning
confidence: 99%